Primary Greatness : The 12 Levers of Success - Covey, Stephen R. (New York Simon & Schuster, 2015)
"This book is a collection of several of [Sean Covey's] father's best essays that have never appeared in book form before and aren't well known. But they are vintage Stephen Covey and contain some of his best thinking"--Foreword.
Keywords: Success--Psychological aspects -- Influence (Literary, artistic, etc.) -- Self-actualization (Psychology)